A genome-wide search for new imprinted genes in the human placenta identifies DSCAM as the first imprinted gene on chromosome 21. (January 2019) - Allach El Khattabi, Laïla; Backer, Stéphanie; Pinard, Amélie; Dieudonné, Marie-Noëlle; Tsatsaris, Vassilis; Vaiman, Daniel; Dandolo, Luisa; Bloch-Gallego, Evelyne; Jammes, Hélène; Barbaux, Sandrine
Abstract We identified, through a genome-wide search for new imprinted genes in the human placenta, DSCAM (Down Syndrome Cellular Adhesion Molecule) as a paternally expressed imprinted gene. Our work revealed the presence of a Differentially Methylated Region (DMR), located within intron 1 that might regulate the imprinting in the region. This DMR showed a maternal allele methylation, compatible with its paternal expression. We showed that DSCAM is present in endothelial cells and the syncytiotrophoblast layer of the human placenta. In mouse, Dscam expression is biallelic in foetal brain and placenta excluding any possible imprinting in these tissues. This gene encodes a cellular adhesion molecule mainly known for its role in neurone development but its function in the placenta remains unclear. We report here the first imprinted gene located on human chromosome 21 with potential clinical implications.